Adventures in the West - Barker, Jane Valentine, 1930-; Downing, Sybil; Wilson, Robert F., (Robert Franklin), 1937- (Boulder, Colo. : Pruett Pub. Co., 1979)
Presents four stories from Colorado's history based on incidents involving Zebulon Pike, Lieutenant Fremont and Kit Carson, Fort Misery, and a stampede of buffalo.
Bibliography: p. 37.
Keywords: Frontier and pioneer life -- Colorado -- Fiction; Colorado -- History -- To 1876 -- Fiction; Short stories